Pelaksanaan Pendidikan Inklusi Di Sekolah Sivana Motessori Makassar - Sapu, Asna Krisna; Ansar, Ahlun; Arismunandar; Naoval, Muh.; Khairunnisa (Irfani, 2026)
Inclusive education represents the fulfillment of every citizen’s right to access education without discrimination, as mandated by the Regulation of the Minister of National Education No. 70 of 2009. This study is motivated by the importance of implementing an educational system that provides equal learning opportunities for all children, including those with special needs. Sivana Montessori School in Makassar was selected as the research site because it applies the Montessori approach, emphasizing independence, freedom of learning, and respect for individual potential within an inclusive setting. This study aims to describe the implementation of inclusive education at the school, including admission policies for students with special needs, assessment processes, the development of Individualized Education Programs (IEP), curriculum implementation, the role of special education teachers, parental involvement, and challenges encountered. A descriptive qualitative approach was employed through observation, semi-structured interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, with source and method triangulation to ensure validity. The findings indicate that inclusive education at Sivana Montessori has been implemented systematically by integrating the National Curriculum with Montessori-based hands-on and multisensory learning. Collaboration among teachers, parents, disability organizations, and government support plays a crucial role. However, challenges remain, particularly limited disability-friendly facilities and the need for continuous teacher training